Child sexual abuse: a public health problem in India - Atmakuri, Lakshmana Rao; Shaik, Aminabee; Thota, Suguna Leelavathi (Springer, 2024)
This book is about child sexual abuse in India. Child sexual abuse (CSA) is a serious and wide-spread problem in India as it is in many parts of the world today. The trauma associated with sexual abuse can contribute to arrested development, as well as a host of psychological and emotional disorders, that some children and adolescents may never overcome. This edited book discusses the nature and incidence of the sexual abuse of minors in India and presents an overview of research findings to date. Socio-cultural and familial risk factors involved in CSA are discussed. Common symptoms and disorders associated with sexual abuse are outlined. The book also provides guidance on child protective services, coordinated response in preventing child abuse, mental health, and law enforcement. Finally, it discusses cognitive behavioral interventions to overcome the trauma caused due to sexual abuse